(untitled) (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
Abstract This paper examines aging as a psychic process, connecting concepts from Freud, Klein, Winnicott, Jung, and Lacan with IBGE demographic data (2010–2022) and projections to 2032. It analyzes the subjective transformations of aging and proposes clinical techniques — therapeutic journaling, art therapy, reading groups, and body expression — to foster symbolization and libidinal investment. Grounded in psychoanalytic listening, the study portrays aging as a period of elaboration and meaning-making rather than decline. It concludes that elderly individuals, by integrating losses and re-signifying experiences, preserve desire and symbolic capacity, reaffirming the relevance of psychoanalysis in the clinical understanding of aging.